Heteroatom-Coordinated Fe–N4 Catalysts for Enhanced Oxygen Reduction in Alkaline Seawater Zinc-Air Batteries - Fang, Wenhan; Xu, Kailong; Wang, Xinlei; Zhu, Yuanhang; Li, Xiuting; Liu, Hui; Li, Danlei; Wu, Jun (Nano-Micro Letters, 2026)
Seawater zinc-air batteries are promising energy storage devices due to their high energy density and utilization of seawater electrolytes. However, their efficiency is hindered by the sluggish oxygen reduction reaction (ORR) and chloride-induced degradation over conventional catalysts. In this study, we proposed a universal synthetic strategy to construct heteroatom axially coordinated Fe–N4 single-atom seawater catalyst materials (Cl–Fe–N4 and S–Fe–N4). X-ray absorption spectroscopy confirmed their five-coordinated square pyramidal structure. Systematic evaluation of catalytic activities revealed that compared with S–Fe–N4, Cl–Fe–N4 exhibits smaller electrochemical active surface area and specific surface area, yet demonstrates higher limiting current density (5.8 mA cm−2). The assembled zinc-air batteries using Cl–Fe–N4 showed superior power density (187.7 mW cm−2 at 245.1 mA cm−2), indicating that Cl axial coordination more effectively enhances the intrinsic ORR activity. Moreover, Cl–Fe–N4 demonstrates stronger Cl− poisoning resistance in seawater environments. Chronoamperometry tests and zinc-air battery cycling performance evaluations confirmed its enhanced stability. Density functional theory calculations revealed that the introduction of heteroatoms in the axial direction regulates the electron center of Fe single atom, leading to more active reaction intermediates and increased electron density of Fe single sites, thereby enhancing the reduction in adsorbed intermediates and hence the overall ORR catalytic activity. Highlights: 1 A universal synthetic strategy was proposed to construct heteroatom axially coordinated Fe–N4 single-atom seawater catalyst materials (Cl–Fe–N4 and S–Fe–N4). 2 The Cl–Fe–N4 catalyst achieves a limiting current density of 5.8 mA cm−2 and a half-wave potential of 0.931 V vs. RHE in alkaline synthetic seawater, outperforming commercial Pt/C (40 wt%). 3 The seawater-based zinc-air battery fabricated with Cl–Fe–N4 demonstrates a power density of 187.7 mW cm−2 at 245.1 mA cm−2 and maintains stable cycling performance for 200 h.